2006
DOI: 10.1073/pnas.0600931103
|View full text |Cite
|
Sign up to set email alerts
|

Backsteps induced by nucleotide analogs suggest the front head of kinesin is gated by strain

Abstract: The two-headed kinesin motor harnesses the energy of ATP hydrolysis to take 8-nm steps, walking processively along a microtubule, alternately stepping with each of its catalytic heads in a hand-over-hand fashion. Two persistent challenges for models of kinesin motility are to explain how the two heads are coordinated (''gated'') and when the translocation step occurs relative to other events in the mechanochemical reaction cycle. To investigate these questions, we used a precision optical trap to measure the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 54 publications
10
156
2
Order By: Relevance
“…The dimer then enters the ATP-waiting state with 1 mobile tethered head with ADP still bound to it. In this model, the nucleotidefree head is the leading one according to data indicating that nucleotide dissociation preferentially occurs in the forward-positioned head (29). Two possible configurations for the ATP-waiting state, consistent with our FPM data are shown.…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…The dimer then enters the ATP-waiting state with 1 mobile tethered head with ADP still bound to it. In this model, the nucleotidefree head is the leading one according to data indicating that nucleotide dissociation preferentially occurs in the forward-positioned head (29). Two possible configurations for the ATP-waiting state, consistent with our FPM data are shown.…”
Section: Methodssupporting
confidence: 70%
“…Strain between the motor domains or the distinct orientation of the neck linkers on each motor domain provokes an asymmetry (20,21,(29)(30)(31) so that ADP is released from the tethered head when it binds to the microtubule in the forward position but not in the trailing one. An alternative model for the ADP release gate, independent of the microtubule lattice, has been proposed based on the observation that the gate and tubulin binding can operate in the presence of free tubulin (19).…”
Section: Discussionmentioning
confidence: 99%
“…Recent singlemolecule (SM) experiments have shown that, with each stepping motion being strongly coupled to the ATP, the kinesin moves toward the (ϩ) ends of MTs by taking discrete 8-nm steps (3-7) in a hand-over-hand fashion (4,7,8). Although the ultimate understanding of kinesin's motility is still far from completion, the SM experiments (3)(4)(5)(6)(7)(8)(9), together with the series of kinetic ensemble measurements (10)(11)(12)(13) and theoretical studies (14)(15)(16)(17)(18)(19), begin providing glimpses to the physical principle of how kinesin walks.…”
Section: F Irst Recognized By Means Of Their Close Relationship Betweenmentioning
confidence: 99%
“…For kinesin, the T and the E state of each motor head are strongly bound whereas the D state is only weakly bound to the filament [13][14][15]. In order to make a forward mechanical step, the trailing head must detach from the filament whereas the leading head must be firmly attached to it.…”
Section: Network Representationsmentioning
confidence: 99%
“…Thus, these chemical transitions take much longer than the mechanical steps. When the catalytic domain of one motor head is occupied by ADP, this head is only loosely bound to the microtubule [13][14][15] and most likely to unbind from it.…”
Section: Introductionmentioning
confidence: 99%